Service-oriented architecture governance for the services driven enterprise - Marks, Eric A. (John Wiley & Sons, 2008)
"If you are leading the charge to adopt service-oriented architecture (SOA) within your enterprise, you know that successful implementation of SOA is challenging to the point that many organizations just avoid confronting the SOA governance issue altogether. Capturing a wealth of practical experience and lessons learned in what has become the hottest topic in business, Service-Oriented Architecture Governance for the Services Driven Enterprise insightfully presents a proven model of Enterprise SOA Governance, augmented by a governance modeling design framework and a body of governance modeling tools and techniques to meet all of your enterprise SOA governance requirements."--Jacket